Data and processes linking vulnerability assessment to adaptation decision-making on climate change in Norway - Næss, Lars Otto; Norland, Ingrid Thorsen; Lafferty, William M.; Aall, Carlo (Global environmental change, 2006)
The article focuses on the use of climate change vulnerability assessments in a local decision-making context, with particular reference to recent studies in Norway. We focus on two aspects of vulnerability assessments that we see as key to local decision-making: first, the information generated through the assessments themselves, and second, the institutional linkages to local level decision-making processes. Different research approaches generate different types of data. This is rarely made explicit, yet it has important implications for decision-making. In addressing these challenges we propose a dialectic approach based on exchange, rather than integration of data from different approaches. The focus is on process over product, and on the need for anchoring vulnerability assessments in local decision-making processes. In conclusion, we argue that there is unlikely to be one single ‘correct’ assessment tool or indicator model to make vulnerability assessments matter at a local level.